1984
DOI: 10.1099/00222615-17-3-335
|View full text |Cite
|
Sign up to set email alerts
|

A chemotyping scheme for clinical isolates of Haemophilus influenzae

Abstract: SUMMARY. A total of 464 Haemophilus influenzae strains, most of them fresh clinical isolates, have been classified by chemotyping-a combination of auxotyping and biotyping. Seven auxotests and four other biochemical tests allowed recognition of 56 types. These were to a degree site-specific. H. inJIuenzae of capsular type b proved almost without exception to belong to one chemotype, and 24 of 33 strains assigned to this chemotype were capsulated. When surgical-ward isolates of H . injluenzae were typed, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…These data suggested that the requirement for methionine and histidine might be associated with nontypeable' H. influenzae. In a recent study of 437 nontypeable strains of H. influenzae in which susceptibility profiles were not reported, methionine was required by only 7 strains (1.6%), whereas histidine and hypoxanthine were required by 133 (30%) and 252 (58%) strains, respectively (14). Our results with Ampr NBLP nontypdable strains for the latter two markers are consistent since 13 of 41 strains (31%) required histidine and 32 of 43 strains (74%) required hypoxanthine.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…These data suggested that the requirement for methionine and histidine might be associated with nontypeable' H. influenzae. In a recent study of 437 nontypeable strains of H. influenzae in which susceptibility profiles were not reported, methionine was required by only 7 strains (1.6%), whereas histidine and hypoxanthine were required by 133 (30%) and 252 (58%) strains, respectively (14). Our results with Ampr NBLP nontypdable strains for the latter two markers are consistent since 13 of 41 strains (31%) required histidine and 32 of 43 strains (74%) required hypoxanthine.…”
Section: Resultssupporting
confidence: 86%
“…Our results with Ampr NBLP nontypdable strains for the latter two markers are consistent since 13 of 41 strains (31%) required histidine and 32 of 43 strains (74%) required hypoxanthine. In contrast, a requirement for methionine does appear to be associated with this resistance phenotype, since 43% (9 of 21) of the Ampr NBLP nontypeable isolates required this amino acid for growth versus 1.6% of the isolates in the study of Tebbutt (14).…”
Section: Resultsmentioning
confidence: 88%
“…Early in the present decade, techniques were developed for classifying serotype b isolates on the basis of variation in the electrophoretic mobility patterns of the major outer-membrane proteins (OMPs) [7][8][9][10] and lipopolysaccharide [11,12], serologic diversity in lipopolysaccharide antigens [9,13,14], and other phenotypic characters [15][16][17]. An examination of 51 serotype b isolates recovered from children in St. Louis with invasive infections identified nine distinctive OMP pattern subtypes and demonstrated that five subtypes, designated as IH, lL, 2H, 2L, and 3L, accounted for 9211,70 of the strains [18].…”
mentioning
confidence: 99%
“…Electrophoretic studies of enzymes and outer membrane proteins (OMPs) have revealed extensive genetic diversity and a clonal structure in populations of serotype b strains and unencapsulated, serologically nontypable strains (5), but little is known concerning the population genetics and evolutionary relationships of strains of capsule types a, c, d, e, and f. Some genetic information has been obtained by metabolic typing (6)(7)(8), human immunoglobulin Al protease typing (9,10), electrophoretic profiling of lipopolysaccharides (11) and OMPs (12), and restriction fragment length polymorphism (RFLP) analysis of the IgAl protease gene (13) and the capsule synthesis genes (12,14), but these studies have not indexed variation in the genome as a whole and, hence, have not provided an adequate basis for inferring evolutionary relationships.…”
mentioning
confidence: 99%